Integrated cost and environmental impact assessment of management options for dredged sediment. (1st February 2022) - Svensson, Nina; Norén, Anna; Modin, Oskar; Karlfeldt Fedje, Karin; Rauch, Sebastien; Strömvall, Ann-Margret; Andersson-Sköld, Yvonne
Graphical abstract: Highlights: Integrated cost and environmental assessment of sediment management options. Life-cycle assessment of climate impact and scoring of other environmental impacts. The integrated assessment highlights synergies as well as counteracting effects. Abstract: Large quantities of sediment must be dredged regularly to enable marine transport and trade. The sediments are often polluted, with e.g. metals, which limits the management options. The aim of this study has been to assess costs and environmental impacts (impact on climate, marine organisms, etc.) of different management options for polluted dredged sediment, by combining life-cycle assessment (LCA) of the climate impact, scoring of other environmental aspects and a cost evaluation. This approach has been used to study both traditional and new management alternatives for a real port case. The studied options include landfilling, deep-sea disposal, construction of a port area using a stabilization and solidification (S/S) method, and a combination of the aforementioned methods with the innovative option of metal recovery through sediment electrolysis. The LCA showed that deep-sea disposal had the lowest climate impact. The assessment of the other environmental impacts showed that the result varied depending on the pollution level and the time perspective used (short or long-term). Using sediment for construction had the highest climate impact, although other environmental impacts were comparably low. Electrolysis was found to be suitable for highly polluted sediments, as it left the sediment cleaner and enabled recovery of precious metals, however the costs were high. The results highlight the complexity of comparing different environmental impacts and the benefits of using integrated assessments to provide clarity, and to evaluate both the synergetic and counteracting effects associated with the investigated scenarios and may aid early-stage decision making.